A Theory of Charitable Fund-Raising with Costly Solicitations - Name-Correa, Alvaro J; Yildirim, Huseyin (American Economic Review, 2013)
We present a theory of charitable fund-raising in which it is costly to solicit donors. We fully characterize the solicitation strategy that maximizes donations net of fund-raising costs. It is optimal for the fund-raiser to target only the “net contributors”––donors who would give more than their solicitation costs. We show that as the income inequality increases, so does the level of the public good, despite a (potentially) non-monotonic fund-raising strategy. This implies that costly fund-raising can provide a novel explanation for the non-neutrality of income redistributions and government grants often found in empirical studies.